2021
DOI: 10.1080/13102818.2021.1920462
|View full text |Cite
|
Sign up to set email alerts
|

Common bean as a potential crop for future food security: an overview of past, current and future contributions in genomics, transcriptomics, transgenics and proteomics

Abstract: turkey; b Department of Field crops, Faculty of agriculture, Bolu abant İzzet Baysal university, Bolu, turkey; c State Key laboratory for conservation and utilization of Subtropical agro-bioresources, South china agricultural university, guangzhou, pR china; d cRea Research center for cereal and industrial crops, Bologna, italy;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 277 publications
(227 reference statements)
1
49
0
Order By: Relevance
“…Common bean is one of the most important legume crops used frequently in the diets of the human populations of the developing and least developed countries, and therefore crops like common bean are considered as “poor man’s meat”. Moreover, common bean is referred to as a “grain of hope” as its seeds are rich sources of various mineral elements crucial for human health ( Nadeem et al, 2021a ). The present work was done with an objective of characterizing the mini core collection of common bean germplasms from Turkey, an important area of diversity for common bean, to find the promising accessions with high Mg contents in the common bean seeds and also to unlock the chromosomal region associated with this mineral element and to discuss whether the genomic regions identified here are novel QTLs or whether they fall into the same genetic region reported earlier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common bean is one of the most important legume crops used frequently in the diets of the human populations of the developing and least developed countries, and therefore crops like common bean are considered as “poor man’s meat”. Moreover, common bean is referred to as a “grain of hope” as its seeds are rich sources of various mineral elements crucial for human health ( Nadeem et al, 2021a ). The present work was done with an objective of characterizing the mini core collection of common bean germplasms from Turkey, an important area of diversity for common bean, to find the promising accessions with high Mg contents in the common bean seeds and also to unlock the chromosomal region associated with this mineral element and to discuss whether the genomic regions identified here are novel QTLs or whether they fall into the same genetic region reported earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, this crop is cultivated all over the world and a total of 34 mha area was under common bean cultivation globally during 2020, resulting in a production of 27.5 mtones ( FAO, 2022 ). Earlier studies confirmed that common bean was originated and domesticated in Mesoamerica and arrived in Europe through Columbian exchange ( Rodiño et al, 2006 ; Gioia et al, 2013 ; Nadeem et al, 2021a ), and then to Turkey through Ottoman traders. Turkey is considered a hotspot for agricultural biodiversity for most of the crops we use in our kitchen today ( Nadeem et al, 2018 ; Nadeem et al, 2020a ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, researchers determined genes related to improved leaf and seed mass in common bean ( Schmutz et al, 2014 ). Although successful gene transformation studies are limited in common bean, many indirect and direct gene transfer attempts have been done (reviewed by Nadeem et al (2021 )). One of those attempts involved the construction of transgenic lines that display tolerance to golden mosaic geminivirus (BgMV-BR) via transferring Rep-TrAP-REn and BC1 genes to common bean by the biolistic method ( Aragão et al, 1998 ).…”
Section: Applications In Legumesmentioning
confidence: 99%
“…Association mapping is one of the modern breeding approaches used to identify genetic loci that determine desired traits ( Lewontin and Kojima, 1960 ). Association mapping has several advantages over the bi-parental QTL mapping approach ( Yu and Buckler, 2006 ; Tian et al, 2011 ; Wen et al, 2014 ; Nadeem et al, 2021 ). For example, association mapping explores the allelic diversity that exists in the diverse germplasm, while QTL mapping can examine the allele variation present in only two parental lines.…”
Section: Introductionmentioning
confidence: 99%